The Constitutional Law on Human Rights - Castillo Córdova, Luis (2019)
In a Constitutional State of Law, constitutional law of human rights could not be reduce to Constitutional rules. It calls for the developing of material and formal categories that would allow to display human rights, from the constitutional summit of the legal system to all domains with legal relevance to the human being. Constitutional law of human rights claims first of all, for a material concept of human rights that could place the human being as start and ending point. It also claims for the building of a concept of rule that could allow to respect the authority of its legal maker sources, and at the same time could be flexible enough to work with the constitutional rules produced at the domestic law, as far as with those who could come from abroad. Only in this way could be possible to attend with adequacy, also argumentative, the different problems created by the aggregate validity of human rights in the current times.